(untitled) (International Journal of Engineering and Computer Science, 2018)
During the attention at a new object our senses try to sense and analyze that particular object and make us interact with them. But to know the complete information about a particular object we should go through it in detail by surfing on net or asking the relevant person for information. Instead, sixth sense technology can be used to immediately trace out the whole information about an object as soon as we see it. Sixth Sense technology is a revolutionary way to interface the physical world with digital information. Sixth sense is a wearable gestural interface that augments the physical world around us with digital information and lets us use natural hand gestures to interact with that information. This paper focuses on and makes us aware with the sixth sense technology which provides an integration of the digital world with the physical world; it helps us understand how the sixth sense device had overpowered the five natural senses